(untitled) (Research, Society and Development, 2026)
New technologies are present in virtually all sectors of society, forming part of people’s daily lives in their homes, workplaces, and educational institutions. These transformations have significantly influenced how individuals learn, also impacting face-to-face education and strengthening the expansion of Distance Education (DE). In this context, digital technologies broaden the possibilities of access to knowledge and promote the democratization of education. Furthermore, they contribute positively to pedagogical practice, promoting greater interaction between students, teachers, and tutors. Thus, this work aims, through a descriptive literature review, to analyze the main technologies used in Distance Education, highlighting their models, tools, and virtual learning environments. It is observed that, despite the challenges of distance education, the main obstacle lies not in the use of this modality, but in the way it is planned, implemented, and conducted.